2019
DOI: 10.1016/j.cellsig.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Individual Smad2 linker region phosphorylation sites determine the expression of proteoglycan and glycosaminoglycan synthesizing genes

Abstract: Individual Smad2 linker region phosphorylation sites determine the expression of proteoglycan and glycosaminoglycan synthesizing genes. Cls (2018),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 49 publications
4
27
0
Order By: Relevance
“…Additionally, the cell-type specific activation of individual MAPK JNK, p38 and ERK has been demonstrated to phosphorylate the regulatory linker region of Smad2 protein [13,49]. As Smad signalling is critical to fibroblast activation and fibrosis induced by activin A [49,55], inhibition of Smad2 signalling by usage of MAPK inhibitors might have contributed to the suppressed XYLT1 expression increase in activin A-stimulated cells shown in this study. Several studies using human VSMC have demonstrated the dependency of PG synthesis on the phosphorylation of the Smad2 linker region.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Additionally, the cell-type specific activation of individual MAPK JNK, p38 and ERK has been demonstrated to phosphorylate the regulatory linker region of Smad2 protein [13,49]. As Smad signalling is critical to fibroblast activation and fibrosis induced by activin A [49,55], inhibition of Smad2 signalling by usage of MAPK inhibitors might have contributed to the suppressed XYLT1 expression increase in activin A-stimulated cells shown in this study. Several studies using human VSMC have demonstrated the dependency of PG synthesis on the phosphorylation of the Smad2 linker region.…”
Section: Discussionsupporting
confidence: 54%
“…The involvement of p38 MAPK in the TGFβ pathway promoted XT-I mRNA and the activity increase were observed in cultured human cardiac fibroblasts stimulated with TGFβ1 and corresponds with an elevated amount of digested GAG content in cardiac tissues from patients with myocardial fibrosis [27]. Additionally, in a recent study JNK and p38 were shown to be involved in growth factor thrombin or IL-1β-induced XYLT1 mRNA expression increase in vascular smooth-muscle cells or primary chondrocyte cells [43,49].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…While GPCR transactivation of EGFR requires MMP stimulation, the activation of TGFBR1 occurs through cytoskeletal rearrangement which activates ROCK signalling and cell-surface integrins ( 13 , 16 , 122 ). We previously found that the GPCR agonist thrombin transactivates the EGFR and TGFBR1 to stimulate the expression of enzymes involved in the hyperelongation of glycosaminoglycan chains on the proteoglycan, biglycan ( 123 , 124 ) which is associated with increased lipid retention in the vessel wall initiating atherosclerosis ( 125 , 126 ). We have described that GPCR transactivation of either receptor is occurring via completely different mechanisms and the identification of a common mechanism can attenuate all GPCR-mediated GAG chain elongation ( 127 , 128 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the order of parameter and radiality from high to low as the standard, a total of 15 core proteins were screened, which includes the SMAD family variant 2 (SMAD2), CCAAT enhancer binding protein beta (CEBPB), conversion factor 1 (TGFB1), mitotic checkpoint serine/threonine protein kinase B (BUB1B), output 1 (XPO1), cell division cycle protein 27 (CDC27), early young granulocyte leukemia variant 1 (PML) transcription, protein phosphatase 2 support subunits X5 (PPP2R1B), cellar protein 1 (CAV1), autosomal histone lysine methylation transferase (EHMT2) 2, transforming growth factor beta receptor 1 (TGFbR1), histone (Hist1H2BM), retinol X receptor α (RXRA), adhesive protein complex (Rad21), and E3 ubiquitin protein ligase (Nedd4) (Figure 5). SMAD proteins encoded by their respective genes are signal transducers and transcriptional modulators that mediate multiple signaling pathways [17,18]. This protein mediates the signal of the transforming growth factor-(TGF-) beta, and thus regulates multiple cellular processes, such as cell proliferation, apoptosis, and differentiation [19,20].…”
Section: Ppi Network Analysis and Core Disturbed Genementioning
confidence: 99%